High-strength flame-retardant plastic-wood board and manufacturing process thereof
By modifying polyvinyl chloride and adding mullite fiber additives, the problems of low strength and poor flame retardant properties of plastic wood boards are solved, and plastic wood boards with high strength and high flame retardant properties are achieved, improving the safety of materials and service life.
Patent Information
- Application Number
- CN202411358434.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing plastic wood boards have low strength and poor flame retardant properties, which are difficult to withstand external impacts, and produce toxic gases during combustion, which poses safety hazards.
By modifying polyvinyl chloride, ternary flame retardant elements of nitrogen, phosphorus and sulfur are introduced to form an integrated expanded flame retardant based on polyvinyl chloride, and mullite fiber additives are added to plastic wood boards to improve the binding of materials. Sex and strength.
It realizes the high strength and high flame retardant properties of plastic wood boards, reduces the generation of toxic gases during combustion, and improves the safety and service life of the material.
Smart Images

Figure CN119463391A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a high-strength flame-retardant plastic wood board and a manufacturing process thereof. Background Art
[0002] Plastic wood board, as the name implies, is a board made of a mixture of plastic and wood powder. As a new and environmentally friendly material, plastic wood board has gradually received widespread attention and application. From outdoor floors, railings, gardening facilities to indoor furniture, decorative panels, etc., plastic wood boards can be seen. Among many plastic substrates, polyvinyl chloride has good processing performance, weather resistance and chemical stability, so polyvinyl chloride is usually used as the main plastic component in plastic wood boards.
[0003] Since plastic wood boards not only have the natural beauty and environmental protection of traditional wood, but also have the durability of plastic materials, plastic wood boards can exhibit functions such as moisture-proof and waterproof. However, the plastic wood boards currently on the market generally have the problems of brittle texture and low strength, and are difficult to withstand external force impacts generated during use or transportation. In addition, the flame retardant properties of plastic wood boards are poor. Although polyvinyl chloride itself can have certain flame retardant properties, the presence of a large amount of halogen in its structure will produce toxic gases during combustion, posing a major safety hazard. This has led to the gradual restriction of the application of plastic wood boards. Therefore, it is urgent to develop plastic wood boards with high strength and high flame retardant properties.
[0004] The invention patent with application number CN202110066550.3 discloses a sulfonate-based biochar flame-retardant wood-plastic board and its production method. By adding sulfonated carbon to the formula of the wood-plastic board, an expansion flame-retardant system is formed with heavy calcium and resin in the wood-plastic board to improve the flame retardant properties of the wood-plastic board. Therefore, functional modifications such as flame retardancy of the wood-plastic board can be achieved by starting from the formula. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a high-strength flame-retardant plastic wood board and a manufacturing process thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A process for producing a high-strength flame-retardant plastic wood board, wherein the plastic wood board is produced from the following raw materials in parts by weight:
[0008]
[0009] The manufacturing process comprises the following steps:
[0010] The first step is to mix the modified polyvinyl chloride, stabilizer, azodicarbonamide and foaming regulator, control the mixing temperature to be 130-140°C, and the mixing time to be 30-40 minutes to form a premix;
[0011] The second step is to mix wood flour, mullite fiber additive, light calcium, plasticizer, lubricant and antioxidant at a temperature of 80-100°C, then add them to the premix, and mix them at a temperature of 140-150°C for 20-30 minutes to form a precursor;
[0012] The third step is to control the extrusion temperature to 200-210℃ and the pressure to 20-40MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0013] As a further embodiment of the present invention, the wood powder is selected from poplar wood powder with a particle size of 60-100 meshes.
[0014] As a further embodiment of the present invention, the preparation method of the modified polyvinyl chloride comprises the following steps:
[0015] Step A, adding polyvinyl chloride to cyclohexanone, stirring, until a uniform solution is formed, then adding 2-amino-6-hydroxybenzimidazole to the solution, then gradually raising the temperature to 65-75° C., maintaining the temperature for 3-6 hours, cooling and discharging to obtain an intermediate;
[0016] Step B, adding the intermediate to N,N-dimethylformamide, stirring, introducing nitrogen to remove oxygen, and then adding phosphorus oxychloride compound and catalyst. After adding, raising the temperature to 60-70°C, keeping warm and stirring for 6-9 hours, discharging the material, and obtaining modified polyvinyl chloride.
[0017] As a further embodiment of the present invention, in step A, the mass ratio of the polyvinyl chloride to 2-amino-6-hydroxybenzimidazole is 1:0.1-0.2.
[0018] As a further embodiment of the present invention, in step B, the phosphorus oxychloride compound is dibenzyl phosphorus oxychloride or diphenyl chlorophosphate.
[0019] As a further embodiment of the present invention, in step B, the catalyst is triethylamine or pyridine.
[0020] In the above technical scheme, 2-amino-6-hydroxybenzimidazole is first used as a modifier to undergo a substitution reaction with the halogen substituent in the polyvinyl chloride structure, thereby introducing the benzimidazole containing a hydroxyl substituent into the polyvinyl chloride molecular chain to obtain an intermediate, and then through the action of a catalyst, the hydroxyl substituent in the intermediate structure is further reacted with the phosphorus oxychloride group in the phosphorus oxychloride compound structure, thereby introducing the phosphorus-based flame retardant compound into the polyvinyl chloride structure to obtain a modified polyvinyl chloride. In the modified polyvinyl chloride structure, the benzimidazole can provide a gas source, the phosphorus-containing group provides an acid source, and the polyvinyl chloride can be used as a carbon source to form an integrated expansion flame retardant system.
[0021] As a further embodiment of the present invention, the preparation method of the mullite fiber additive comprises the following steps:
[0022] Step ①, dispersing mullite fiber in toluene, then adding 2-chloroethyl isocyanate and dibutyltin dilaurate, stirring evenly after adding, then controlling the temperature to 60-70°C, keeping warm and stirring for 2-4 hours, stopping heating, centrifuging out the solid material, and obtaining halogenated mullite fiber;
[0023] Step ②, N, N'-bis (2-hydroxyethyl) -N, N'-bis (trimethoxysilyl) propyl) ethylenediamine and alkaline activator are added to 1,4-dioxane, and the mixture is kept warm at 50-60 ° C for 1-2 hours, and then halogenated mullite fiber is added, ultrasonic dispersion is performed for 20-40 minutes, and then the temperature is increased to 70-80 ° C, and the mixture is kept warm for 3-6 hours, and then 4,4'-dichlorodiphenyl sulfone is added, and the mixture is kept warm and stirred for 8-12 hours, and then the temperature is reduced and the material is discharged, and the solid matter is centrifuged to obtain the mullite fiber additive.
[0024] As a further embodiment of the present invention, in step ②, the alkaline activator is sodium hydride.
[0025] In the above technical scheme, 2-chloroethyl isocyanate is first used as a modifier, and the highly active isocyanate group in its structure is used to react with the hydroxyl group on the surface of the mullite fiber to obtain a mullite fiber containing a halogen substituent. Then, N,N'-bis(2-hydroxyethyl)-N,N'-bis(trimethoxysilylpropyl)ethylenediamine is used as a bridging agent, and 4,4'-dichlorodiphenyl sulfone is used as a chain extender. Under the action of an alkaline activator, continuous substitution occurs, thereby forming a macromolecular modifier connected by an ether bond on the surface of the mullite fiber, namely, a mullite fiber additive.
[0026] As a further solution of the present invention, the stabilizer is a calcium zinc stabilizer; the plasticizer is dioctyl phthalate; the lubricant is polyethylene wax or stearic acid; the antioxidant is antioxidant 1010 or antioxidant 1076; and the foaming regulator is an acrylate foaming regulator.
[0027] A high-strength flame-retardant plastic wood board is made by adopting the above-mentioned manufacturing process.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention first modifies polyvinyl chloride and reduces the halogen substituents in the polyvinyl chloride structure by substitution reaction. At the same time, nitrogen, phosphorus and sulfur ternary flame retardant elements are introduced to form an integrated intumescent flame retardant based on polyvinyl chloride. This can not only reduce the toxic gases generated during combustion, but also utilize the efficient flame retardant effect of the integrated intumescent flame retardant to quickly form an intumescent carbon layer to prevent further combustion, thereby making the prepared plastic wood board have excellent flame retardant properties.
[0030] (2) The macromolecular modification structure on the surface of the mullite fiber additive prepared by the present invention contains a large number of siloxane groups, which can interact with wood powder during high-temperature extrusion. It also contains a large number of benzene ring structures, which can produce conjugation with the benzene ring in the modified polyvinyl chloride structure. Therefore, the mullite fiber additive can act as a "bridge" to enable wood powder and modified polyvinyl chloride to have better bonding with each other, making the structure of the plastic wood board more compact, which is beneficial to improving the strength of the plastic wood board. Mullite fiber can also effectively exert its own advantages in the plastic wood board, so that the strength of the plastic wood board can be further enhanced.
[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is the FT-IR graph of modified polyvinyl chloride. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Preparation Example 1
[0036] Preparation of modified polyvinyl chloride:
[0037] Step A, adding 3 g of polyvinyl chloride with a degree of polymerization of 650 to cyclohexanone, stirring, and forming a uniform solution, then adding 0.5 g of 2-amino-6-hydroxybenzimidazole to the solution, and then gradually raising the temperature to 70° C., maintaining the temperature for 4 hours, and then cooling and discharging to obtain an intermediate;
[0038] Step B, add 2.4g of the intermediate to N,N-dimethylformamide, stir well, introduce nitrogen to remove oxygen, then add 0.3g of diphenyl chlorophosphate and 0.1g of triethylamine. After the addition, raise the temperature to 65°C, keep stirring for 8h, and then discharge the material to obtain modified polyvinyl chloride.
[0039] Modified polyvinyl chloride was made into potassium bromide tablets and subjected to infrared analysis test. The results are as follows Figure 1 As shown, 3302cm -1 The absorption peak at 3000cm is the characteristic absorption peak of NH in the secondary amine group; -1 ~3100cm -1 The absorption peak at 2800 cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring skeleton. -1 ~3000cm -1 The absorption peak at 1290 cm is the characteristic absorption peak of CH of methylene. -1 The absorption peak that appears at is the characteristic absorption peak of P=O.
[0040] Preparation Example 2
[0041] Preparation of mullite fiber additives:
[0042] Step ①, 5g of mullite fiber is dispersed in toluene, and then 1.8g of 2-chloroethyl isocyanate and 0.1g of dibutyltin dilaurate are added, and after adding, the mixture is stirred evenly, and then the temperature is controlled to 65°C, and after stirring for 3h, the heating is stopped, and the solid material is centrifuged to obtain halogenated mullite fiber;
[0043] Step ②, add 0.3g of N,N'-bis(2-hydroxyethyl)-N,N'-bis(trimethoxysilylpropyl)ethylenediamine and 0.05g of sodium hydride to 1,4-dioxane, keep warm at 50°C for 2h, then add 1.5g of halogenated mullite fiber, ultrasonically disperse for 30min, then increase the temperature to 75°C, keep warm for 4h, add 0.5g of 4,4'-dichlorodiphenyl sulfone, continue to keep warm and stir for 9h, cool and discharge, centrifuge the solid to obtain the mullite fiber additive.
[0044] The TS9000 organic element analyzer was used to analyze the percentage of organic elements in the mullite fiber additive. 0.3 g of the sample was taken as a test sample. The test results showed that the nitrogen content of the sample was 7.81%, and the sulfur content was 8.65%.
[0045] Example 1
[0046] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0047]
[0048] The manufacturing process of the plastic wood board comprises the following steps:
[0049] The first step is to mix the modified polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, control the mixing temperature to be 130° C., and the mixing time to be 40 minutes to form a premix;
[0050] Step 2: Mix wood flour, mullite fiber additive, light calcium, dioctyl phthalate, polyethylene wax, and antioxidant 1010 at 80°C, then add them to the premix, and mix them at 140°C for 30 minutes to form a precursor;
[0051] The third step is to control the extrusion temperature to 200°C and the pressure to 20MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0052] The wood powder is selected from poplar powder with a particle size of 100 mesh; the preparation method of modified polyvinyl chloride is shown in Preparation Example 1; the preparation method of mullite fiber additive is shown in Preparation Example 2; the model of foaming regulator is HF-901, and the following are the same.
[0053] Example 2
[0054] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0055]
[0056] The manufacturing process of the plastic wood board comprises the following steps:
[0057] The first step is to mix the modified polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, and control the mixing temperature to be 135° C. and the mixing time to be 30 minutes to form a premix;
[0058] Step 2: Mix wood flour, mullite fiber additive, light calcium, dioctyl phthalate, stearic acid, and antioxidant 1076 at 90°C, add them to the premix, and mix them at 150°C for 20 minutes to form a precursor;
[0059] The third step is to control the extrusion temperature to 210°C and the pressure to 30MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0060] Example 3
[0061] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0062]
[0063] The manufacturing process of the plastic wood board comprises the following steps:
[0064] The first step is to mix the modified polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, and control the mixing temperature to be 140° C. and the mixing time to be 30 minutes to form a premix;
[0065] Step 2: Mix wood flour, mullite fiber additive, light calcium, dioctyl phthalate, stearic acid, and antioxidant 1076 at 100° C., then add them to the premix, and mix them at 150° C. for 20 minutes to form a precursor;
[0066] The third step is to control the extrusion temperature to 210°C and the pressure to 40MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0067] Comparative Example 1
[0068] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0069]
[0070]
[0071] The manufacturing process of the plastic wood board comprises the following steps:
[0072] The first step is to mix polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, and control the mixing temperature to be 135° C. and the mixing time to be 30 minutes to form a premix;
[0073] Step 2: Mix wood flour, mullite fiber additive, light calcium, dioctyl phthalate, stearic acid, and antioxidant 1076 at 90°C, add them to the premix, and mix them at 150°C for 20 minutes to form a precursor;
[0074] The third step is to control the extrusion temperature to 210°C and the pressure to 30MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0075] Comparative Example 2
[0076] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0077]
[0078]
[0079] The manufacturing process of the plastic wood board comprises the following steps:
[0080] The first step is to mix the modified polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, and control the mixing temperature to be 135° C. and the mixing time to be 30 minutes to form a premix;
[0081] Step 2: Mix wood flour, mullite fiber, light calcium, dioctyl phthalate, stearic acid, and antioxidant 1076 at 90°C, add them into the premix, and mix them at 150°C for 20 minutes to form a precursor;
[0082] The third step is to control the extrusion temperature to 210°C and the pressure to 30MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0083] Comparative Example 3
[0084] A high-strength flame-retardant plastic wood board is made of the following raw materials in parts by weight:
[0085]
[0086]
[0087] The manufacturing process of the plastic wood board comprises the following steps:
[0088] The first step is to mix the modified polyvinyl chloride, calcium zinc stabilizer, azodicarbonamide and foaming regulator, and control the mixing temperature to be 135° C. and the mixing time to be 30 minutes to form a premix;
[0089] Step 2: Mix wood flour, light calcium, dioctyl phthalate, stearic acid and antioxidant 1076 at 90°C, add them into the premix, and mix them at 150°C for 20 minutes to form a precursor;
[0090] The third step is to control the extrusion temperature to 210°C and the pressure to 30MPa, extrude the precursor material and shape it to obtain the plastic wood board.
[0091] Test Case
[0092] The plastic wood panels in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for various properties, and the results are shown in the following table:
[0093]
[0094]
[0095] Note: The bending strength test is carried out according to the standard GB / T 9341-2008; the compressive strength test is carried out according to the standard GB / T 1041-2008; the flame retardant performance test is carried out according to the standard GB / T 2408-2021.
[0096] The analysis and test results show that by modifying polyvinyl chloride and adding mullite fiber modifier, the prepared plastic wood board can have good mechanical strength and flame retardant properties.
[0097] After replacing modified polyvinyl chloride with conventional polyvinyl chloride, on the one hand, a conjugation effect cannot be formed between the modified polyvinyl chloride and the mullite fiber modifier, and the bonding between the materials becomes poor, resulting in a slight impact on the mechanical properties of the material, but a significant decrease in the flame retardant properties.
[0098] After the mullite fiber modifier is replaced with mullite fiber, it cannot play the role of a "bridge", the bonding force between the components is greatly reduced, and the mullite fiber cannot effectively exert its own advantages. Therefore, the mechanical properties are significantly reduced. After the mullite fiber modifier is directly removed, the mechanical properties are further reduced.
[0099] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A process for producing a high-strength flame-retardant plastic wood board, characterized in that: The plastic wood board is made of the following raw materials in parts by weight: The manufacturing process comprises the following steps: The first step is to mix the modified polyvinyl chloride, stabilizer, azodicarbonamide and foaming regulator, control the mixing temperature to be 130-140°C, and the mixing time to be 30-40 minutes to form a premix; The second step is to mix wood flour, mullite fiber additive, light calcium, plasticizer, lubricant and antioxidant at a temperature of 80-100°C, then add them to the premix, and mix them at a temperature of 140-150°C for 20-30 minutes to form a precursor; The third step is to control the extrusion temperature to 200-210℃ and the pressure to 20-40MPa, extrude the precursor material and shape it to obtain the plastic wood board.
2. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 1 is characterized in that: The wood powder is selected from poplar wood powder with a particle size of 60-100 meshes.
3. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 1 is characterized in that: The preparation method of the modified polyvinyl chloride comprises the following steps: Step A, adding polyvinyl chloride to cyclohexanone, stirring, until a uniform solution is formed, then adding 2-amino-6-hydroxybenzimidazole to the solution, then gradually raising the temperature to 65-75° C., maintaining the temperature for 3-6 hours, cooling and discharging to obtain an intermediate; Step B, adding the intermediate to N,N-dimethylformamide, stirring, introducing nitrogen to remove oxygen, and then adding phosphorus oxychloride compound and catalyst. After adding, raising the temperature to 60-70°C, keeping warm and stirring for 6-9 hours, discharging the material, and obtaining modified polyvinyl chloride.
4. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 3 is characterized in that: In step A, the mass ratio of the polyvinyl chloride to 2-amino-6-hydroxybenzimidazole is 1:0.1-0.
2.
5. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 3 is characterized in that: In step B, the phosphorus oxychloride compound is dibenzyl phosphorus oxychloride or diphenyl chlorophosphate.
6. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 3 is characterized in that: In step B, the catalyst is triethylamine or pyridine.
7. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 1 is characterized in that: The preparation method of the mullite fiber additive comprises the following steps: Step ①, dispersing mullite fiber in toluene, then adding 2-chloroethyl isocyanate and dibutyltin dilaurate, stirring evenly after adding, then controlling the temperature to 60-70°C, keeping warm and stirring for 2-4 hours, stopping heating, centrifuging out the solid material, and obtaining halogenated mullite fiber; Step ②, N, N'-bis (2-hydroxyethyl) -N, N'-bis (trimethoxysilyl) propyl) ethylenediamine and alkaline activator are added to 1,4-dioxane, and the mixture is kept warm at 50-60 ° C for 1-2 hours, and then halogenated mullite fiber is added, ultrasonic dispersion is performed for 20-40 minutes, and then the temperature is increased to 70-80 ° C, and the mixture is kept warm for 3-6 hours, and then 4,4'-dichlorodiphenyl sulfone is added, and the mixture is kept warm and stirred for 8-12 hours, and then the temperature is reduced and the material is discharged, and the solid matter is centrifuged to obtain the mullite fiber additive.
8. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 7, characterized in that: In step ②, the alkaline activator is sodium hydride.
9. The manufacturing process of a high-strength flame-retardant plastic wood board according to claim 1, characterized in that: The stabilizer is a calcium zinc stabilizer; the plasticizer is dioctyl phthalate; the lubricant is polyethylene wax or stearic acid; the antioxidant is antioxidant 1010 or antioxidant 1076; and the foaming regulator is an acrylic foaming regulator.
10. A high-strength flame-retardant plastic wood board, characterized in that: The method is manufactured by the manufacturing process as claimed in claim 1.
Citation Information
Patent Citations
A sulfonic acid-based biochar flame-retardant wood-plastic composite board and its production method
CN112745603B
Wood plastic plate and its preparation method
CN102746594A
Reactive flame retardant containing phosphoryl benzimidazole and preparation method of reactive flame retardant
CN112250903A
High-strength environment-friendly flame-retardant polypropylene composite material and preparation method thereof
CN113896981A
Nitrogen-phosphorus synergistic flame-retardant functional montmorillonite modified PVC wood-plastic plate and preparation method thereof
CN114196129A
Cited By
Flame-retardant polyvinyl chloride composite board and processing method thereof
CN120518909A